Enhancing soil quality for sustainable agricultural practices in Subak rice fields - Susila, Ketut Dharma; Ginting, Debby Clara Br; Adnyana, I Made; Saifulloh, Moh; Arthagama, I Dewa Made (Journal of Degraded and Mining Lands Management, 2024)
Understanding the soil quality of Subak rice fields in Bali is crucial for maintaining agricultural sustainability. This study aimed to explore aspects of soil quality, identify limiting factors, and offer guidance on sustainable land management. Utilizing survey methods, laboratory analysis, and soil quality determination, soil samples were selectively collected from each land unit (LU). LU selection was based on overlays of Subak zonation, soil type, slopes, rainfall, and elevation using Geographic Information System (GIS) techniques. Key soil quality indicators were assessed, including bulk density, texture, porosity, moisture content, pH, organic carbon, cation exchange capacity, base saturation, and nutrients (N, P, K). Overall, soil quality in the study area is classified as good in all LUs, but with significant variations in Soil Quality Index (SQI) values, suggesting the need for tailored management recommendations. Limiting factors include soil texture, organic carbon content, total nitrogen, available phosphorus, and biomass C. Recommended soil management practices include single plow tillage and the application of manure, urea, and SP-36 fertilizer on paddy fields. This approach aims to enhance land productivity sustainably while upholding environmental conservation and the principles of Subak, which have historically maintained a balanced and sustainable agricultural ecosystem.